Harrowing Blindness and Ocular Morbidity in a Himalayan Village (Nepal Journal of Epidemiology, 2016)
To address this terrible situation, we propose the following solutions: in the short term, conduct regular eye health camps with appropriate management locally. In the long term, to strengthen primary eye care and integrate it into general health, by training primary health care workers in primary eye care (more specifically assessing visual acuity) establishing adequate referral channels. Currently, unfortunately, much of eye care service delivery remains centered on the district headquarters and accessible places, with other remote regions left unattended. We hope our report will awaken all concerned to the dire need for equitable eye care across the country.